Collective Honesty? Experimental Evidence on the Effectiveness of Honesty Nudging for Teams - Dunaiev, Yuri; Khadjavi, Menusch (Frontiers in Psychology, 2021)
A growing literature in economics studies ethical behavior and honesty, as it is imperative for functioning societies in a world of incomplete information and contracts. A majority of studies finds more pronounced dishonesty among teams compared to individuals. Scholars identified certain nudges as effective and cost-neutral measures to curb individuals’ dishonesty, yet little is known about the effectiveness of such nudges for teams. We replicate a seminal nudge treatment effect, signing on the top of a reporting form versus no signature, with individuals and confirm the original nudge treatment effect. We further run the same experiment with teams of two that have to make a joint reporting decision. Our results show the effectiveness of the nudge for teams, which provides further confidence in the applicability of the nudge.